Analisis Faktor-Faktor Penting Pada Studi Profil Pelajar Pancasila (International Forum of Researchers and Lecturers, 2023)
Student profile Pancasila has an important role in education because Pancasila is the basis of the Indonesian state which contains the values of national and state life. This triggered a lot of research related to the profile of Pancasila students. The purpose of this research is to capture the research landscape related to the Pancasila student profile. The method used is bibliometric analysis. Data obtained from the Scopus database which has been improved. The results showed that the number of publications related to Pancasila and Student increased every year from 2016 to 2020. The highest number of documents was in Indonesia, the highest number of documents were in the institution or university